Psychoactive drug consumption among truck-drivers: a systematic review of the literature with meta-analysis and meta-regression - DINI, G. (J Prev Med Hyg, 2019)
Few studies have assessed the extent of psychoactive drug consumption in the occupational setting. The trucking sector, in particular, is an important cause for concern, since psychoactive substance use has a relevant impact on the drivers’ health and safety, increasing the risk of injuries and traffic accidents, potentially affecting the general public health as well. A systematic review of the literature and meta-analysis was performed in order to provide Occupational Health Professionals and policy-makers with an updated epidemiological perspective regarding this important issue. The results showed a prevalence of overall drug consumption of 27.6% [95%CI 17.8-40.1], particularly high considering illicit CNS-stimulants (amphetamine consumption of 21.3% [95%CI 15.7-28.1], and cocaine consumption of 2.2% [95%CI 1.2-4.1]). It appears that truck-drivers choose stimulant substances as a form of performance enhancing drug, in order to increase productivity. However, chronic and high dose consumption has been shown to decrease driving skills, placing these professional drivers at risk for health and road safety. Further research is required, particularly in Europe, in order to fill the knowledge gap and improve the strength of evidence.